2021
DOI: 10.1111/ppc.12965
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a nurse‐led intervention program on compassion fatigue, burnout, compassion satisfaction, and psychological distress in nurses: A randomized controlled trial

Abstract: Purpose This study evaluated the effect of a nurse‐led intervention program on compassion fatigue, burnout, compassion satisfaction, and psychological distress in nurses. Design and Methods A randomized controlled trial was conducted. A total of 48 clinical nurses were randomly allocated to intervention or control groups. The nurse‐led intervention program was based on a cognitive‐behavioral approach. The study outcomes were compassion fatigue, burnout, compassion satisfaction, and psychological distress. Find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
(65 reference statements)
0
12
0
Order By: Relevance
“…Twenty articles were excluded after reading 35 full texts. Finally, 15 RCTs were included in the review [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]. The flow diagram of the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty articles were excluded after reading 35 full texts. Finally, 15 RCTs were included in the review [69][70][71][72][73][74][75][76][77][78][79][80][81][82][83]. The flow diagram of the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…From the analysis of journals, we inferred that studies in CF and PR fields mainly focused on nurses and social workers and their psychological problems, which can also be found from the analysis of categories. Nurses are usually to exposed various stressful work environments in daily work, such as the death of patients, violence, acute conditions, and the suffering of patients, which they are often unable to deal with ( Yilmaz et al, 2018 ; Partlak Günüşen et al, 2021 ). For clinical social workers on the frontline, they are also faced with a serious human service crisis: clients with mental health problems exacerbated by the stress related to COVID-19 and individuals with no previous behavioral health issues suffering from symptoms due to social isolation, quarantine, and the drastic change in daily life.…”
Section: Resultsmentioning
confidence: 99%
“…Lower levels of burnout stimulate nurses to engage more actively in their work, fostering increased work motivation and the allocation of greater energy and concentration. This manifests as heightened diligence and precision in their work, resulting in proactive prevention and avoidance of potentially risky events and ultimately leading to heightened levels of safety behaviours (Partlak et al., 2021). Consequently, self‐efficacy influences safety behaviours through the chain mediation of burnout and work engagement, thus establishing the chain mediation pathway of ‘self‐efficacy → burnout → work engagement → safety behaviours.’ Previous studies have demonstrated that various psychological interventions, such as cognitive behavioural therapy, positive thinking stress reduction therapy (Othman et al., 2023), psychoeducational group intervention (Bailey et al., 2021), emotional release therapy, etc.…”
Section: Discussionmentioning
confidence: 99%